GAMBARAN PERKEMBANGAN MOTORIK HALUS PADA BAYI DENGAN ASI EKSKLUSIF DI PUSKESMAS SALO PINRANG TAHUN 2021 - A.Tri Putri Namirah; Andi Tihardimanto; Syatirah Jalaluddin; Utami Murti Pratiwi; Muh. Sadiq Sabri (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
Background: Child development in Indonesia still needs serious attention. The rate of delayed growth and development is still quite high, with about 5-10% experiencing general developmental delays. Malnutrition in the first years of life causes brain cells to decrease by 15-20%. This process causes developmental disorders such as psychomotor, cognitive and social behavioral disorders. Objective : to see the picture of fine motor development in infants with exclusive breastfeeding at the Salo Pinrang Health Center in 2021. Methods : The research design used is observational with a cross sectional approach. The number of samples in this study amounted to 135 samples. Data analysis used in this study using the SPSS application univariate analysis test then see an overview based on the sample distribution results. Results: It was found that 93 babies (68.89%) were exclusively breastfed and 42 babies (31.11%) were not exclusively breastfed. And obtained that babies who have questionable fine motor skills are 31 babies (68.89%) and babies who have appropriate fine motor skills are 104 babies (77.04%). Conclusion: Most of the fine motor development in infants at the Salo Pinrang Health Center is appropriate because most infants at the health center have received exclusive breastfeeding